2022
DOI: 10.3390/genes13122300
|View full text |Cite
|
Sign up to set email alerts
|

Pantothenate and L-Carnitine Supplementation Improves Pathological Alterations in Cellular Models of KAT6A Syndrome

Abstract: Mutations in several genes involved in the epigenetic regulation of gene expression have been considered risk alterations to different intellectual disability (ID) syndromes associated with features of autism spectrum disorder (ASD). Among them are the pathogenic variants of the lysine-acetyltransferase 6A (KAT6A) gene, which causes KAT6A syndrome. The KAT6A enzyme participates in a wide range of critical cellular functions, such as chromatin remodeling, gene expression, protein synthesis, cell metabolism, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…52 Skin sections were incubated for 45 minutes at 37°C and for 1 hour at room temperature with the following primary antibodies: rabbit polyclonal anti-TRPV1 (working concentration 1 µg/ml; diluted 1:350; Abcam, Cambrige, UK), 53 rabbit polyclonal anti-MMP9 (working concentration 1 µg/ml; diluted 1:400; Abbiotec, San Diego, CA, USA), rabbit polyclonal anticyclooxygenase-2 (COX-2) (working concentration 0.5 µg/ml; diluted 1:400; Cayman Chemical, Ann Arbor, MI, USA), 54 and mouse monoclonal antisuperoxide dismutase-1(SOD-1) (working concentration 2 µg/ml; diluted 1:100; Santa Cruz Biotechnology, Dallas, TX, USA). 5557 Then, the sections were incubated for 1 hour with specific biotinylated secondary antibodies (Vector Laboratories, Newark, CA, USA) and subsequently conjugated with avidin-biotin peroxidase complex (Vector Laboratories, Burlingame, CA, USA). The reaction products were visualized using 0.33% hydrogen peroxide and 0.05% 3,3ʹ-diaminobenzidine tetrahydrochloride, as chro-mogen (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…52 Skin sections were incubated for 45 minutes at 37°C and for 1 hour at room temperature with the following primary antibodies: rabbit polyclonal anti-TRPV1 (working concentration 1 µg/ml; diluted 1:350; Abcam, Cambrige, UK), 53 rabbit polyclonal anti-MMP9 (working concentration 1 µg/ml; diluted 1:400; Abbiotec, San Diego, CA, USA), rabbit polyclonal anticyclooxygenase-2 (COX-2) (working concentration 0.5 µg/ml; diluted 1:400; Cayman Chemical, Ann Arbor, MI, USA), 54 and mouse monoclonal antisuperoxide dismutase-1(SOD-1) (working concentration 2 µg/ml; diluted 1:100; Santa Cruz Biotechnology, Dallas, TX, USA). 5557 Then, the sections were incubated for 1 hour with specific biotinylated secondary antibodies (Vector Laboratories, Newark, CA, USA) and subsequently conjugated with avidin-biotin peroxidase complex (Vector Laboratories, Burlingame, CA, USA). The reaction products were visualized using 0.33% hydrogen peroxide and 0.05% 3,3ʹ-diaminobenzidine tetrahydrochloride, as chro-mogen (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Modification of histones can be influenced by increasing the substrates and this may be a potential mechanism of treatment in Arboleda‐Tham syndrome 31 . Experiments in fibroblasts have demonstrated that acetylation is improved by treatment using L‐carnitine and pantothenate (vitamin B5), two readily available dietary supplements 35 . The impact of this treatment is not yet known on neural models of the disease, which may be more relevant to human disease affecting the brain, whilst another unknown is what therapeutic range that would be optimal for treatment.…”
Section: Mendelian Disorders Of Chromatin Machinery – Influencers Of ...mentioning
confidence: 99%